2007
DOI: 10.1203/01.pdr.0000250198.22735.20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron-Unsaturated Human Lactoferrin on Hydrogen Peroxide-Induced Oxidative Damage in Intestinal Epithelial Cells

Abstract: Human milk (HM) contains various bioactive antioxidants. Lactoferrin (Lf) has been assumed to be one of the major antioxidants in HM. We examined the antioxidative properties of iron-unsaturated human Lf (apo-hLf, the major form of Lf in HM) in two intestinal epithelial cell lines: (1) An intestinal epithelial cell line (IEC-6) were preincubated for 24 h with either 50 g/mL of apo-hLf, iron-saturated human Lf (holo-hLf), iron-unsaturated bovine transferrin (apo-bTf), or 800 ng/mL of the iron-chelating compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 32 publications
2
28
2
1
Order By: Relevance
“…On the other hand, Shoji et al demonstrated that Lf acts as an antioxidant in intestinal epithelial cells. 30) And also, we found that LPS caused oxidative damage by decreasing superoxide dismutase activity in Caco-2 cells (data not shown). Additional studies are needed, but it is conceivable to hypothesize that Lf might play a role in reducing the oxidative stress induced by LPS.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, Shoji et al demonstrated that Lf acts as an antioxidant in intestinal epithelial cells. 30) And also, we found that LPS caused oxidative damage by decreasing superoxide dismutase activity in Caco-2 cells (data not shown). Additional studies are needed, but it is conceivable to hypothesize that Lf might play a role in reducing the oxidative stress induced by LPS.…”
Section: Discussionmentioning
confidence: 79%
“…This antioxidant barrier includes enzymes as well as non-enzymatic components. Human breast milk contains either non-enzymatic antioxidants (among others coenzyme Q, lactoferrin and vitamins A, E and C) [2][3][4][5] or antioxidant enzymes. 6,7 In vitro, human breast milk antioxidants were observed to decrease hydrogen peroxide-induced oxidative damage in intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In vitro, human breast milk antioxidants were observed to decrease hydrogen peroxide-induced oxidative damage in intestinal epithelial cells. 3,4 Antioxidant properties of human breast milk support the natural antioxidant barrier of neonates and infants. Lower levels of oxidative stress are observed in breastfed infants when compared with those receiving infant formulas, 8,9 including the antioxidant-enriched formulas.…”
Section: Introductionmentioning
confidence: 99%
“…44 However, Shoji et al reported that lactoferrin capacity to protect against H 2 O 2 cell toxicity decreases after binding with iron. 45 The MSc1 reactions to pH changes and oxidative conditions (after binding with iron), along with its nanoscale size ( Figure S3), supports MSc1 as an efficient agent for proper iron redistribution in the body and for properly breaking down the vicious cycle of inflammation and OS. MSc1 did not cause any loss of hepatic iron supplies.…”
mentioning
confidence: 81%